Identification of Learning Challenges Towards the Curriculum at SDN 5 Jangkar - Ariyanti, Nindya Suci; Murtinasari, Frida; Hidayatin, Nur (International Journal of Trends in Mathematics Education Research, 2025)
This study aims to identify obstacles in the learning process at SDN 5 Jangkar, Situbondo Regency, which include limited facilities, lack of conducive environmental support, and low public awareness of the importance of education. These factors have an impact on the quality of the teaching and learning process and student learning outcomes at SDN 5 Jangkar. This study uses a descriptive method with data collection techniques through interviews, observations, and documentation, with a focus on the implementation of the curriculum in the classroom to be more organized and in accordance with the planning. The results of the study indicate that the main challenge in learning at SDN 5 Jangkar is the inconsistency of the implementation of the curriculum with the planned learning design. Therefore, this study is expected to provide an in-depth description of the challenges faced by schools in implementing the curriculum and formulate strategies to optimize the learning process.